Pengaruh Praktik Meditasi terhadap Pemulihan Pasca Stroke: Pendekatan Kualitatif - Ratnasari Ratnasari; Lauw Acep (Jurnal Rumpun Ilmu Kesehatan, 2025)
Stroke not only causes physical impairment but also affects the psychological and emotional condition of patients, such as stress, anxiety, and depression. Meditation, especially mindfulness meditation and conscious breathing, has developed as a complementary therapy believed to help reduce stress levels and improve focus and quality of life. This study aims to explore the experiences of stroke patients who practice meditation during their rehabilitation process. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with five stroke patients who regularly participated in meditation sessions at a rehabilitation clinic in Surabaya. Data were analyzed through data reduction techniques, thematic categorization, and conclusion drawing. The results show that meditation has positive effects in three main aspects: reducing anxiety and stress, improving focus and self-awareness, and increasing motivation during physical therapy. The study concludes that meditation has the potential to become an effective complementary intervention in post-stroke recovery